The Effect of Warm Compresses on the Intensity of Dysmenorrhea Pain in Adolescents - Rosi Melisa Angow; Widia Shofa Ilmiah (International Journal of Medicine and Health, 2025)
Dysmenorrhea, which is common in adolescent girls, is a painful menstrual cycle that frequently interferes with daily activities, both in the classroom and in social situations. Dysmenorrhea is a common condition that needs particular care as a reproductive health concern, notably among young people. Both pharmacological and non-pharmacological approaches can be used to treat dysmenorrhea. The use of warm water compresses is a simple, inexpensive, and effective non-pharmacological approach. By increasing blood vessel dilatation, enhancing blood circulation, lowering muscular tension, and lowering pain perceptions, warm water compresses aid in alleviating dysmenorrhea symptoms. The objective of this study is to assess the impact of warm compresses on the severity of dysmenorrhea pain scales in teenage girls at the Buntalo Community Health Center. The design of this trial was pre-experimental, using a one-group pretest-posttest technique. Using a purposive sampling method, a sample of 20 respondents was chosen. The Wilcoxon test was used to conduct the data analysis. According to the data, there was a statistically significant reduction in pain intensity, with a Z value of -4.065 and a p-value of 0.000 (p < 0.05). The average pain scale decreased from 2.95 to 1.80. Based on these findings, it is reasonable to conclude that warm water compresses are helpful in alleviating dysmenorrhea pain in young women. One of the suggestions for non-pharmacological treatments to help alleviate dysmenorrhea symptoms in adolescents is anticipated to be the outcome of this research.